Experts’ Opinion on Immunity and Nutrition to Support Key Cognitive Functions - Sekartini, Rini; Surapsari, Juwalita; Oktarina, Molly Dumakuri; Wiguna, Tjhin; Pasiak, Taufiq Fredrik; Basrowi, Ray Wagiu; Kartjito, Melissa Stephanie; Wasito, Erika (Indonesian Nutrition Association, 2023)
The interaction of micronutrients and macronutrients has been shown to have a significant impact on children's cognitive development. Furthermore, proper nutrition helps a child's immune system avoid infection and disease, which can impair nutrient absorption and lead to deficiency. Microbiotas in the gut play critical roles in body physiology, including nutrient absorption, infection resistance and immune system development. Furthermore, it is known that the gut microbiota influences immune cell maturation. Finally, these three factors are thought to influence neurogenesis and cognitive development. A virtual meeting was held with five invited experts to gain a better understanding of the relationship between nutritional factors, the immune system and cognitive development.